Profiles of family-focused adverse experiences through childhood and early adolescence: The ROOTS project a community investigation of adolescent mental health - Dunn, Valerie J (BioMed Central, 2011)
BACKGROUND: Adverse family experiences in early life are associated with subsequent psychopathology. This study adds to the growing body of work exploring the nature and associations between adverse experiences over the childhood years. METHODS: Primary carers of 1143 randomly recruited 14-year olds in Cambridgeshire and Suffolk, UK were interviewed using the Cambridge Early Experiences Interview (CAMEEI) to assess family-focused adversities. Adversities were recorded retrospectively in three time periods (early and later childhood and early adolescence). Latent Class Analysis (LCA) grouped individuals into adversity classes for each time period and longitudinally. Adolescents were interviewed to generate lifetime DSM-IV diagnoses using the K-SADS-PL. The associations between adversity class and diagnoses were explored. RESULTS: LCA generated a 4-class model for each time period and longitudinally. In early childhood 69% were allocated to a low adversity class; a moderate adversity class (19%) showed elevated rates of family loss, mild or moderate family discord, financial difficulties, maternal psychiatric illness and higher risk for paternal atypical parenting; a severe class (6%) experienced higher rates on all indicators and almost exclusively accounted for incidents of child abuse; a fourth class, characterised by atypical parenting from both parents, accounted for the remaining 7%. Class membership was fairly stable (~ 55%) over time with escape from any adversity by 14 years being uncommon. Compared to those in the low class, the odds ratio for reported psychopathology in adolescents in the severe class ranged from 8 for disruptive behaviour disorders through to 4.8 for depressions and 2.0 for anxiety disorders. Only in the low adversity class did significantly more females than males report psychopathology. CONCLUSIONS: Family adversities in the early years occur as multiple rather than single experiences. Although some children escape adversity, for many this negative family environment persists over the first 15 years of life. Different profiles of family risk may be associated with specific mental disorders in young people. Sex differences in psychopathologies may be most pronounced in those exposed to low levels of family adversities.